A Simple Spectrophotometric Assay of Sildenafil In Pure and Pharmaceutical Preparations - Muhamad, Yasmeen H (Al-Nahrain Journal of Science, 2018)
A simple and rapid method has been established for the determination of sildenafil in pure and pharmaceuticals. The method is based on the formation of ion-association complex of sildenafil citrate (SC) with metacresol purple (MCP) in acidic buffer solution. The complex can be extracted into chloroform and quantitatively measured at 410 nm. Regression analysis of the standard plot reveals that Beer’s law was obeyed in the concentration range of 3-70 mg L-1 with detection limit of 0.13 mg L-1 and sandell sensitivity of 0.0452 mg.cm-2. The accuracy of the method is evaluated on the basis of recovery test which found to be of 100.2 ±0.42%. The proposed procedure can be applied for the quality control of pure and commercial tablets determination of sildenafil citrate.